Victor of Vita : History of the Vandal persecution - Victor, svatý, asi 430-asi 505 (Translated texts for historians ;, 1992)
Among the peoples who occupied the territories of the Roman Empire in the West in the fifth century, the Vandals are notorious for their persecution of the Catholic inhabitants of Africa. By far the fullest narrative of their doings prior to the time of Justinian is that provided by Victor of Vita, who in 484 wrote the greater part of the work here translated.